PENGEMBANGAN MEDIA BUKU SAKU PADA MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 1 SEKOLAH DASAR - Bella, Lala; Bramianto Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking ability is an important skill to emphasize in Mathematics learning in order to encourage students to learn through knowledge so that students can solve problems and find solutions. Based on observation activities carried out at SDN Cibuntu 02, several problems were found, including learning media only in textbooks, the absence of media that can improve students' critical thinking skills, and the low level of students' critical thinking skills. Thus, from the problems above, it is necessary to develop a supporting teaching material for textbooks, namely in the form of pocket books that can improve students' critical thinking skills. This research aims to determine the validity of the mathematics pocket book on whole number material, determine the effectiveness of the pocket book in improving critical thinking skills, and the practicality of the pocket book being tested at SDN Cibuntu 02. The method in this research is to use research and development methods with the ADDIE model. Validation of the mathematics pocket book is carried out by media expert validators, language experts and material experts. The validity test of the test instrument was carried out by three experts and the reliability test was carried out by 18 class 2 students. The contextual-based pocket book was implemented using a purposive sampling technique with research subjects totaling 29 class 1 students. The practicality test of the contextual-based pocket book was carried out by students. The research results showed that the product validity test was declared valid for use with a percentage of material experts of 89% and media experts of 84%, 91% of language experts in the very appropriate category. The conclusion of this research is that a mathematics pocket book can be used, is effective in improving students' critical thinking skills, and is very practical to implement in mathematics learning.